Physiological and affective responses of 30s x 30s intermittent small-sided game in elite handball players: A new alternative to intermittent running - Ravier, G.; Hassenfratz, C.; Bouzigon, R.; Groslambert, A. (Journal of Human Sport & Exercise, 2019)
Objectives: To compare physiological and affective demands of a novel small-sided game designed in intermittent (30s-30s) regimen opposing 3-a-side field players with 30s-30s shuttle running and handball match play. Methods: Fourteen elite male handball players (age 23.8 ± 4.4 y; body mass 84.0 ± 7.4 kg; height 188 ± 0.06 m) performed 2 periods of 10-min of each experimental exercise in separate occasions. Physiological demand was assessed using mean heart rate, time spent in heart rate intensity zones and post-exercise blood lactate concentration. The difference between `perceived exertion` and `pleasure` determined the affective balance. Results: Small-sided game and shuttle running drills showed similar mean heart rate (88.8 ±2.4 and 90.4 ±2.8 % of peak heart rate, respectively) and time spent in heart rate zones. The match play elicited lower mean heart rate (86.9 ± 3.4 % of peak heart rate, P = 0.05, large ES) than small-sided game and shuttle running. Peak lactate for small-sided game (6.6 ±2.6 mmol/L) was lower than shuttle running (10 ±2.2 mmol/L, P = 0.05, large ES) whereas no significant difference was observed with match play. The small-sided game showed lower affective balance than shuttle running (P = 0.01, large ES). Conclusions: Coaches can be confident in prescribing the small-sided game as a suitable alternative to shuttle running to provide consistent aerobic stimulus with lower affective balance. The small-sided game may be considered as a specific training method in achieving relevant physiological adaptations for handball match play.